Endovascular Repair of Acute Thoraco-abdominal Aortic Aneurysms. (January 2018) - Mascoli, Chiara; Vezzosi, Massimo; Koutsoumpelis, Andreas; Iafrancesco, Mauro; Ranasinghe, Aaron; Clift, Paul; Mascaro, Jorge; Claridge, Martin; Adam, Donald J.
Abstract : Objectives: The outcome of endovascular repair (EVAR) for acute thoraco-abdominal aortic aneurysm (TAAA) is reported and the applicability of the t-Branch off the shelf (OTS) device is determined. Methods: Interrogation of a prospectively maintained database identified all patients who underwent EVAR for acute TAAA between September 2012 (when the first non-elective t-Branch case was performed) and November 2015. Early and medium-term outcomes were analysed. Survival and re-intervention-free survival were calculated by Kaplan–Meier analysis. Results: A total of 39 patients (27 men; mean ± SD age, 72 ± 8 years) were treated for acute symptomatic ( n  = 29) or ruptured ( n  = 10) TAAA (20 anatomical extent I–III, 19 extent IV). Fourteen patients had mycotic aneurysms. The mean aneurysm diameter was 80 ± 20 mm. The mean ± SD follow-up was 21.4 ± 15.4 months. Surgeon modified fenestrated EVAR was used in 24 patients, chimney/periscope EVAR in two, and t-Branch in 13 (33%) patients. Aortic coverage was greater than 40 mm above the coeliac axis in all patients. A total of 127 target vessels (TVs) were preserved (mean 3.3 per patient) and two occluded within 30 days. The 30 day mortality was 26%. Four (10%) patients developed spinal cord ischaemia (SCI): two with paraplegia died within 30 days, and two with paraparesis recovered completely with blood pressure manipulation and cerebrospinal fluid drainage. Estimated overall survival (±SD) at 12 and 24 months was 71.8 ± 7.2% and 63.2 ± 7.9%, respectively. Estimated freedom from re-intervention at 12 and 24 months was 93 ± 4.8% and 85.3 ± 6.8%, respectively. Conclusions: EVAR for acute TAAA is associated with acceptable early and mid-term results in patients who have no other treatment options. Only one third of these patients were suitable for the t-Branch device, indicating that further advances in device design are required to treat the majority of acute TAAA patients with commercially available OTS technology.